Properties, Storage and Germination Behavior of Seeds of Berberis tinctoria Lesch., an Endangered Medicinal Plant from Shola Forests of Western Ghats, India - Sujanapal, P.; Sumod, M.; Chandrasekhara, U. M.; Chandrasekhara Pillai, P. K. (Indian Forester, 2024)
Berberis tinctoria is an endangered plant with restricted population in the Shola forests of the Western Ghats. Lack of information on seed properties, germination pattern and pre-sowing treatment protocols are hampering ex-situ conservation and restoration of this important medicinal plant. In this study, fruit and seed characteristics, changes in moisture content and germination of fresh seeds with time over a period of one month and different pre-sowing treatment on seed germination were investigated. Moisture content (MC) of fresh seeds is found to be 53.3 per cent and germinability was 68.3 per cent, and critical moisture content of B. tinctoria seeds is estimated as 23.3 per cent with a germinability of 46.8 per cent. Seeds stored in different containers (polythene bag, plastic bottle and earthen pot filled with saw dust) and storage conditions [ambient temperature (25 Â°C; RH 50-60%), and low temperature (16Â°C; RH 55%)] showed less than 34.15 % germination within 6-9 days of storage. Seeds subjected to pre-sowing treatments (soaking in water, treating with GA3, and treating with cow dung slurry) did not show significant difference (p>0.05) in their germination percentage. Use of fresh seeds and soaking them in fresh water for 12 hours is recommended as pre-sowing treatment of B. tinctoria for improving mean germination rate.